Effect and Mechanism of Bifidobacterium animalis B94 in the Prevention and Treatment of Liver Injury in Rats - Tianfang Zhang; Jie Wang; Zhao Yao; Lingmei Ni; Yifan Zhao; Shuang Wei; Zuobing Chen; Zuobing Chen (Frontiers in Cellular and Infection Microbiology, 2022)
ObjectiveTo investigate the effect of Bifidobacterium animalis B94 on the prevention and treatment of liver injury in rats and to elucidate the underlying mechanism of this relationship.MethodsSpecific pathogen-free (SPF) rats were selected as the healthy control group, liver injury group and B94 treatment group, with 6 rats in each group. After the model was established, the experimental animals were tested for serum liver function indicators, gut microbiota composition, metabolite composition, and histopathology.ResultsThe albumin/globulin ratio and serum TBA, alanine aminotransferase, aspartate aminotransferase, and indirect bilirubin levels in the B94 treatment group were significantly lower than those in the liver injury group. 16S rRNA analysis showed that the gut microbiota of the three groups of rats were significantly different. Metabolic profile analysis showed that there were significant differences in the gut metabolomes of the three groups. Haematoxylin–eosin staining of the intestinal mucosa and liver tissues showed that the degree of liver and intestinal tissue damage in the B94 treatment group was significantly lower than that in the liver injury group.ConclusionBifidobacterium animalis B94 can affect the process of liver injury in rats by improving liver function, reducing intestinal damage, and regulating gut microbiota and metabolite production.